Screening for Developmental Delays: Descriptive Study of Children Between the Ages of Two-and-a-Half and Six Years - Sari, Atika Permata (KnE Social Sciences, 2025)
Developmental delays remain a concern for educators, parents, and policymakers. Early identification of developmental delays can facilitate the provision of early intervention treatments. This research aims to show the characteristics of developmental delays in children aged two-and-a-half to six years and to investigate the influence of gender on the prevalence of these delays. This study is a descriptive quantitative non-experimental investigation. The sample comprised of 155 participants, and data were collected via the Denver Developmental Screening Test II (DDST II), performed individually. The research findings indicated that 52% of participants exhibited poor growth. The linguistic dimension appears as the most significant indicator of developmental delay relative to other dimensions. Men and women have notable developmental disparities in adaptive fine motor skills. Based on empirical evidence, educators, guardians, and policymakers can implement preventative and promotion initiatives.